EDUKASI MENYIKAT GIGI DENGAN BENAR SEBAGAI UPAYA PENCEGAHAN GIGI BERLUBANG (KARIES) PADA MURID SD NEGERI 4 SUREN KABUPATEN JEMBER - risqi wahyudi; Afnan Septi Mulyani; Alfi Nur Ramadhani; Danny Dwi Firmansyah; Fadli Muhammad Fathoni; Putri Ramadani; Ratna Amelia; Ramadhan Bagus Cahyono; Tuhfatul Hilmits Tsania; Yola Kristina Cendani; Shinta Mayasari (Universitas Majalengka, 2022)
Brushing teeth is the easiest way to maintain dental and oral health. Elementary school age children have a susceptibility to problems with teeth and mouth. Risk factors that are still driving the high prevalence of dental cavities (caries) in children include: incorrect brushing techniques; inappropriate brushing time and frequency; intake of cariogenic food and drink; low supervision from parents; and the lack of knowledge of children on how to maintain dental and oral health. The problem of cavities in children interferes with the growth and development and attendance of children at school. The purpose of the study: to improve the knowledge and skills of students at SD Negeri 4 Suren on how to brush their teeth properly. Research method: the activity was carried out offline at SD Negeri 4 Suren, on Saturday, August 20, 2022. A series of counseling activities included licensing to the principal of SD Negeri 4 Suren, giving a tooth brushing practice pretest, delivering material verbally assisted by poster media, material in in the form of power points, educational videos, followed by a demonstration of phantom teeth followed by hands-on practice, and giving posttest. Results and conclusions: The pretest results showed 2 out of 10 students answered correctly, while the posttest results showed all students answered the questions correctly. This shows that counseling activities increase students' insight into dental and oral health. Keywords: dental health; caries; Suren Village